2013
DOI: 10.1007/s00216-013-6742-3
|View full text |Cite
|
Sign up to set email alerts
|

Lateral-flow enzyme immunoconcentration for rapid detection of Listeria monocytogenes

Abstract: Lateral-flow enzyme immunochromatography coupled with an immunomagnetic step was developed for rapid detection of Listeria monocytogenes in food matrices. The target bacteria was first separated and concentrated by magnetic nanoparticles containing the enzyme and directly applied to the assay system to induce an antigen-antibody reaction without any additional steps. The color signals produced by an enzyme-substrate reaction at a specific site on the immunostrip were found to be directly proportional to the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 35 publications
0
60
1
2
Order By: Relevance
“…The most certain method was used to detect the samples of aseptic milk (Yili) and lamb-steeped liquor (Haoyue) [26]. A series of different concentrations of 16M were artificially inoculated into the pasteurized milk and lamb-steeped liquor (the lamb liquid lapping compound soaked by saline for 24 h) and then detected the 16M with this method as described above.…”
Section: Methodsmentioning
confidence: 99%
“…The most certain method was used to detect the samples of aseptic milk (Yili) and lamb-steeped liquor (Haoyue) [26]. A series of different concentrations of 16M were artificially inoculated into the pasteurized milk and lamb-steeped liquor (the lamb liquid lapping compound soaked by saline for 24 h) and then detected the 16M with this method as described above.…”
Section: Methodsmentioning
confidence: 99%
“…Vitek, API, MICRO-ID (on the basis of the CAMP test), ELISA and nucleic acid assay kits have been developed for identification of L. monocytogenes. For rapid detection of L. monocytogenes in food matrices, lateral flow enzyme immunochromatography together with an immunomagnetic separation has been developed recently (Cho & Irudayaraj 2013). Molecular tools such as PCR, multiplex PCR and realtime PCR employing virulence-associated genes such as the mpl gene, prfA gene (Rossmanith et al 2006) and ssrA gene (O'grady et al 2008) have been found rapid, specific, reproducible and reliable (Portnoy et al 2002;Gianfranceschi et al 2013;Hage et al 2014;Khan et al 2014).…”
Section: Diagnosismentioning
confidence: 99%
“…The color intensity on the T line was negatively correlated with the amount of Salmonella in the sample. Compared to the commonly used sandwich-based strategy [39,40], this LPS mAb and coating antigen-based paper sensor for competitive detection of Salmonella is innovative and greatly simplifies the development of the strip assay. This is because sandwich-based strategy usually needs two mAbs which must be both paired in ELISA and still work in lateral flow assay.…”
Section: Resultsmentioning
confidence: 99%